Answer:
7.
[tex]g(x) = f(x + 1) = [/tex]
(x + 1)² = x² + 2x + 1
as the original function, but the turnaround is now (still at x = 0) at y = 1 instead of y = 0.
and the graph is "narrower". for x = 1 and x = -1, y = 4. for x = 2 and x = -2, y = 9
8.
[tex]g(x) = f(x) - 2[/tex]
= x² - 2
it is exactly the same graph, just 2 units down in y direction (the turnaround is at x = 0. y = -2).
9.
the right answer is D
Step-by-step explanation:
9.
the y values of +x values now become the same values for the -x values. and vice versa.